Using Proximity Technology for Localization in Wireless Sensor Networks - Peter Brida; Martin Matula; Jan Duha (Communications - Scientific letters of the University of Zilina, 2007)
The localization in wireless sensor networks is very important for function of the network (routing…). The objective of the localization process is to determine the position of device (sensor, node) from the information acquired from the reference devices. These devices of course know their location. The aim of the paper is to give a survey of two proximity based location techniques performance. The results of basic proximity based localization techniques are compared with modified (enhanced) proximity technique. It does not belong to the most accurate techniques, but on the other hand, it is a low cost alternative to more expensive techniques.